Maximal Packing with Interference Constraints - Jagannath, Rakshith; Ganti, Radha Krishna; Upadhye, Neelesh S (IEEE Wireless Communications and Networking Conference : [proceedings] : WCNC, 2019)
In this work, we analyze the maximum number of wireless transmitters (nodes) that can be scheduled subject to interference constraints across the nodes. Given a set of nodes, the problem reduces to finding the maximum cardinality of a subset that can concurrently transmit without violating interference constraints. The resulting packing problem is a binary optimization problem, which is NP hard. We propose a semi-definite (SDP) relaxation for the NP hard problem and discuss the algorithm and the quality of the relaxation by providing approximation ratios for the relaxation.